The Effect of Utilization of Sugarcane Bagasse Ash as Partial Substitution of Cement with Silica Fume Added Materials on the Compressive Strength of Concrete - Fahrizal Zulkarnain; Apendi Apendi (Budapest International Research in Exact Sciences (BirEx) Journal, 2022)
Concrete is a very important material used in the construction sector. In this study, the concrete was made using bagasse ash added, which is known to contain high levels of silicates and pozzolans. In addition, to produce better quality concrete, silica fume concrete additive is used as an additional chemical for concrete mixtures. Silica fume itself is used to make better quality concrete. This study used bagasse ash for 3%, 6%, and 9% of the weight of cement, and silica fume concrete additive was used for 15% of the weight of cement. The dimension of the test object used is a cylinder measuring 15 x 30 cm with a concrete age of 14 and 28 days, for a slump value of 60-180 cm. Planning of concrete mix using SNI 03-2834-2000 method. The test carried out is the compressive strength test of concrete. Each variation made 3 specimens, so the total number of specimens was 24 test specimens. The results of the normal concrete research obtained a compressive strength of 21.08 Mpa, at the age of 14 and 30.11 Mpa at the age of 28 days. while the concrete which was mixed with 3% bagasse ash and 15% silica fume was 22.08 MPa at the age of 14 days and 33.46 MPa at the age of 28 days. than 6% bagasse ash concrete and 15% silica fume amounted to 26.1 Mpa at the age of 14 days and 35.13 Mpa at the age of 28 days. and concrete with a mixture of 9% bagasse ash and 15% silica fume was 29.11 MPa at the age of 14 days and 37.14 MPa at the age of 28 days. Optimum compressive strength results occur in concrete with a mixture of 9% bagasse ash and 15% silica fume, which is 38.09% MPa.